The impact of over tourism on Balinese traditional food and beverages as part of image destination - Satrio, Muhammad; Nugraha, Putu Ari; Anggara, Aryadi; Hiyarialvi , Hiyarialvi (Goodwood Publishing, 2025)
Purpose: This study examines how over-tourism affects Balinese traditional food and beverages in terms of market demand, destination image, and long-term sustainability. Methods: A mixed-method design was applied in key culinary areas (Sanur, Ubud, Bangli, Denpasar, and Kintamani) using direct observations, semi-structured interviews with culinary actors, and questionnaires to domestic and international tourists; data were processed descriptively using SPSS-supported analysis. Results: Over-tourism increases demand and sales for iconic foods/beverages (e.g., Nasi Campur Men Weti, Nasi Ayam Kedewatan, Mujair Nyat-nyat, Bungkil Kunyit, Loloh Cemcem, Kopi Kintamani), supporting income growth, business expansion, job creation, and cultural visibility. However, it also triggers higher raw-material costs, supply-chain and logistics disruption, congestion, competition, quality-control pressure, environmental stress, and risks of cultural commodification that can reduce authenticity. Conclusion: Over-tourism delivers strong economic and branding benefits but simultaneously threatens culinary authenticity, service quality, and sustainability without targeted management. Limitation: The study covers selected sites/products and the post-pandemic period (2022–2024); broader external policy/economic drivers were not deeply analyzed. Contribution: The paper provides empirical insights linking over-tourism, culinary systems, and destination image, offering practical implications for policy and culinary-business decision making toward sustainable tourism strategies.